Sacrococcygeal Teratoma: Experience with 36 Patients in a Teritiary Care Hospital - Kundal, VK; Jadhav, A; Gupta, A; Shukla, A; Chaturvedi, V; Kundal, R (Journal of Nepal Paediatric Society, 2015)
Introduction: Sacrococcygeal teratomas (SCT) are the most common solid tumours in the neonatal period, originate from embryonic totipotent cells. Most of them are benign however some that present later in life and have major intra-pelvic component have greater malignant potential. Complete surgical excision provides an excellent prognosis. The aim of this study was to describe the clinical profile, age of presentation, sex distribution, diagnostic evaluation and management of children with a histological confirmed diagnosis of sacrococcygeal teratoma. Material and Methods: Patients with histological diagnosis of sacrococcygeal teratoma during a period from January 2011 to December 2012 were included in this retrospective study. Data collected included age of presentation, sex distribution, symptoms, associated anomalies, diagnostic evaluation, operative approach technique employed, tumour histology, operative complications and outcome. Results: Thirty six patients with diagnosis of sacrococcygeal teratoma were included in the study. Of these children, 58.33% were females and 41.66% were males. The median age at presentation was four days. 69.44% of patients presented during the neonatal period. 77.77% of patients presented with sacrococcygeal mass followed by lower abdominal mass in 11.11%. The tumour was resected by sacral approach in 27 patients and abdomino sacral approach in nine patients. Tumour was resectable in 34 patients and two had incomplete resection. Follow up duration varied from six months to 24 months. Conclusion: Sacrococcygeal teratomas represent a group of benign and malignant lesions of children. Neonates present with benign disease and aggressive lesions are seen as age progresses. Overall survival of SCT is high. J Nepal Paediatr Soc 2015;35(1):89-93